The Effect Of Road Narrowing On The Traffic Characteristics - Widya Baskara, Reza Yoga; Wahyuni, Atik; Hardanignrum, Farida (International Journal of Engineering, Science and Information Technology, 2021)
A problem found in transportation is road narrowing. Road narrowing refers to a condition in which its downstream is smaller than the upstream. This research took place on Ahmad Yani Street at the front of Royal Plaza, Surabaya. The location of this research had a sufficiently high traffic flow. Thus, the road should be able to operate optimally. In fact, there is still a density caused by road narrowing. This research was intended to determine how much the maximum flow, maximum density and free speed on the road before, during and after the narrowing. Besides, this research was carried out to find out the relation of the flow, the traffic density and speed, determine the value of the shock waves during the road narrowing. This research was done on Wednesday and Saturday morning, at 06:00-08:00 and in the afternoon at 16:00-18:00. The calculation performed was based on Greenshield method. The analysis revealed that the largest maximum flow was on the fragment of road before narrowing, which was 2376.30 pcu/hour. The maximum density found on the fragment of road during narrowing was 322.33 pcu/hour, and the highest free speed regarding to the road condition before the narrowing was 57.21 km/hour. The relation between flow, speed and density showed a significant result (R2 0.5). Shock waves obtained were in the mornings and afternoons on Wednesday and Saturday,